Legal Protection for Domestic Investors Based on Investment Agreements in Indonesia - Siregar, Dedi Martua (Research Horizon, 2025)
This study discusses legal protection for domestic investors in investment agreements in Indonesia, especially in the context of cooperation between the private sector and the government and limited liability companies. Domestic investment has an important role in supporting national economic growth, but in practice investors often face legal risks in the form of default, unilateral termination of agreements, and weak law enforcement. Using a normative juridical approach that is descriptive and analytical, this study analyzes various legal provisions that govern investor protection, such as the principle of legal certainty, the principle of pacta sunt servanda, and the right of investors to sue for compensation in accordance with the Civil Code and Law Number 25 of 2007 concerning Investment. The results of the study show that legal certainty and dispute resolution mechanisms are fundamental aspects that determine the effectiveness of legal protection for investors. The state has an obligation to provide assurance, protection, and access to fair legal remedies when there is a violation of the agreement. Therefore, it is necessary to strengthen regulations and legal implementation in order to create a healthy, sustainable investment climate, and encourage the active participation of domestic investors in national economic development.